Influence of different types of light curing units and photoinitiators in microhardness and color of composite resins after immersion in wine - Souza, Morganna Borges de Almeida; Briso, André Luiz Fraga; Ramos, Fernanda de Souza e Silva; de Oliveira Reis, Bruna; dos Santos, Paulo Henrique; Fagundes, Ticiane Cestari (Brazilian Dental Science, 2019)
Abstract Objective: the aim of this study to evaluate the microhardness and color change (?E) of composite resins, light cured with different LEDs, submitted to staining drink. Materials and Methods: Two composite resins with lucerin-TPO (Tetric N-Ceram/ Vit-l-escence) and camphorquinone (Filtek Z350) were select. Specimens (n=120) were prepared. Then were photopolymerized with LED of singlewave or polywave. Microhardness and color evaluations were performed before and after chalanges. Data were evaluated by two-way ANOVA, Tukey's test (p?0,05). Results: No statistically significant difference between the two generations of LEDs was found for microhardness data. Regarding the ?E, statistical difference between the two LEDs was observed for Tetric N- Ceram and Filtek Z350. Conclusion: Compostion of composites appears to have more influence on analyses than the type of LEDs.